Forecasting exchange rate volatility in the presence of jumps - Thomas Busch; Bent Jesper Christensen; Morten Ørregaard Nielsen (Queen's University, Department of Economics, 2005)
We study measures of foreign exchange rate volatility based on high-frequency (5-minute) /DM exchange rate returns using recent nonparametric statistical techniques to compute realized return volatility and its separate continuous sample path and jump components, and measures based on prices of exchange rate futures options, allowing calculation of option implied volatility. We find that implied volatility is an informationally efficient but biased forecast of future realized exchange rate volatility. Furthermore, we show that log-normality is an even better distributional approximation for implied volatility than for realized volatility in this market. Finally, we show that the jump component of future realized exchange rate volatility is to some extent predictable, and that option implied volatility is the dominant forecast of the future jump component.
Keywords: C1; F31; G1; 330; bipower variation; currency options; exchange rates; implied volatility; jumps; realized volatility; Wechselkurs; Devisenoptionsgeschäft; Volatilität; Stochastischer Prozess; Theorie